Thinking about crime : sense and sensibility in American penal culture - Tonry, Michael H. (Studies in crime and public policy., 2004)
Examines the American crime policy. This book explains how the worst policies can be undone and how the avoidable human suffering they produce can be diminished. It presents a treatment of crime as a social problem.